Managing hyperglycemia and diabetes in patients receiving enteral feedings: A health system approach - Mabrey, Melanie E. (Hosp Pract (1995), 2015)
Evidence of poor outcomes in hospitalized patients with hyperglycemia has led to new and revised guidelines for inpatient management of diabetes. As providers become more aware of the need for better blood glucose control, they are finding limited guidance in the management of patients receiving enteral nutrition. To address the lack of guidelines in this population, Duke University Health System has developed a consistent practice for managing such patients. Here, we present our practice strategies for insulin use in patients receiving enteral nutrition. Essential factors include assessing the patients’ history of diabetes, hyperglycemia, or hypoglycemia and timing and type of feedings. Insulin practices are then designed to address these issues keeping in mind patient safety in the event of abrupt cessation of nutrition. The outcome of the process is a consistent and safe method for glucose control with enteral nutrition.